Genetic trends for fertility, udder health and protein yield in Swedish red cattle estimated with different models. (20th February 2017) - Eriksson, S.; Johansson, K.; Hansen Axelsson, H.; Fikse, W.F.
Summary: The aim of this study was to estimate and compare genetic trends in Swedish Red cattle using a full multiple‐trait (MT) model and trait‐group‐wise models for female fertility, udder health and protein yield. Field data for maiden heifers from 1989 and cows with a first and second lactation between 1990 and 2007 were included. (Co)variance components were estimated prior to prediction of breeding values. The estimated genetic trends were clearly favourable for protein yield and udder conformation, and in most cases neutral to favourable for clinical mastitis and calving to first insemination. In maiden heifers, the trends were neutral for number of inseminations per service period. Unfavourable genetic trends were estimated for number of inseminations in the first two lactations, but the trends seemed less unfavourable from evaluations within trait groups compared with when using the full MT model. Excluding maiden heifer data affected genetic trends less than using trait‐group‐wise analyses instead of a full MT model. Unfavourable genetic trends in functional traits may be missed unless the traits are evaluated in a MT model including traits under strong selection.